FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MENGGUNAKAN INTERNET BANKING (STUDI PADA MAHASISWA UNIVERSITAS SYIAH KUALA) - Ermadini Harisa; Nurma Sari (FEB Universitas Syiah Kuala, 2020)
The purpose of this research is to analyze the factors that influence the interest of Syiah Kuala University students using Internet Banking. Sample in this study were 100 students. The data used are primary data obtained using a questionnaire. Data analysis was performed using multiple linear regression analysis. The results of the research show that convenience, risk and trust have a simultaneous effect on the interest of students using Internet Banking. From the research, R Square is 0.511, which means that all independent variables have a joint contribution of 51.1% to the dependent variable, and 48.9% are influenced by other factors.